Environmental Friendliness Analysis of Purse Seine Operated by Km Sumber Baru, Belawan, North Sumatera - Adhiatma Mario Sipahutar; Abdul Kohar Mudzakir; Indradi Setiyanto (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2022)
Purse Seine fishing gear is a fishing gear operated by several fishermen in the WPP NRI 571. Purse seine is a type of fishing gear that classified as surrounding nets, which is an active fishing gear to catch pelagic fish which who generally live in groups in large flocks. The main catch is Mackerel scad (Decapterus spp). The purpose of this study was to determine the level of environmental friendliness of the Purse seine fishing gear in PPS Belawan. The method used in this study is by using a score based on the Code of Conduct for Responsible Fisheries (CCRF) criteria, fish physiology analysis, and also analyze the suitability of fishing gear with the regulation of Permen KP.71 of 2016. Based on the results of the study, it can be concluded that physiologically fish include into fish fit for catching with a total length ranging from 19-24 cm, the average size of the first caught (Lc) at a length of 15 cmFL, the size of the first sentence gonads (Lm) 19.6 cmFL, Km. Sumber Baru does not meet the Regulations of the size of the vessel, and the Purse Seine fishing gear is very environmentally friendly with a score of 32 points.This Lc value is smaller than the Lm value. From this result, it is known that most of the scads caught have not passed the first gonadal maturity size (Lc<Lm), but in terms of the specifications of the fishing gear, they have adjusted to the applicable regulations